Emerging Contaminants from Industrial and Municipal Waste Removal technologies - Barceló, Damià; Petrovic, Mira.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
The group of non-regulated contaminants termed “emerging contaminants” mainly comprises products used in large quantities in everyday life, such as human and veterinary pharmaceuticals, personal care products, surfactants and surfactant residues, plasticizers and various industrial additives. The occurrence of “emerging contaminants” in wastewaters, and their behavior during wastewater treatment and production of drinking water are key issues in the re-use of water resources. Emerging Contaminants from Industrial and Municipal Waste focuses on innovative treatment technologies for the elimination of emerging contaminants from wastewater and drinking water. The respective treatment processes, such as membrane bioreactors, photocatalysis, ozonation and advanced oxidation are dealt with in detail. The book also discusses sources and occurrence of emerging contaminants in municipal and industrial waste, giving a concise and critical overview of state-of-the-art analytical methods for their identification. Further important aspects covered by the book include the acute and chronic effects and overall impact of emerging contaminants on the environment.
Removal of Emerging Contaminants in Wastewater Treatment: Conventional Activated Sludge Treatment -- Membrane Bioreactor (MBR) as an Advanced Wastewater Treatment Technology -- Removal of Emerging Contaminants in Water Treatment by Nanofiltration and Reverse Osmosis -- Ozone-Based Technologies in Water and Wastewater Treatment -- Removal of Emerging Contaminants in Waste-water Treatment: Removal by Photo-catalytic Processes -- Behavior of Emerging Pollutants in Constructed Wetlands -- Input of Pharmaceuticals, Pesticides and Industrial Chemicals as a Consequence of Using Conventional and Non-conventional Sources of Water for Artificial Groundwater Recharge -- Advanced Sorbent Materials for Treatment of Wastewaters -- Conclusions and Future Research Needs -- Erratum to Membrane Bioreactor (MBR) as an Advanced Wastewater Treatment Technology.
Keywords: Water pollution; Water-supply.; Environmental law; Environmental policy; Air pollution; Ecotoxicology; Environmental pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Industry/Water Technologies; Environmental Law/Policy/Ecojustice.; Atmospheric Protection/Air Quality Control/Air Pollution; Ecotoxicology; Terrestrial Pollution